Inside Cover: Donor‐Acceptor Fluorescent Molecular Rotors Appended with Benzocrown Ethers as Doubly Twisted Intramolecular Charge Transfer Based Ratiometric Acidic pH Sensors (Asian J. Org. Chem. 2/2016). Issue 2 (8th January 2016) - Umar, Shahida; Jha, Ajay Kumar; Goel, Atul
Abstract : Highly fluorescent molecular rotors based on benzocrown ethers have been synthesized. The dimethylamino‐appended benzocrown ether has fascinating photophysical properties with good quantum yield and dual emission bands in polar solvents due to the unique doubly twisted intramolecular charge transfer (DT‐ICT) phenomenon. The dual fluorescence property of the molecular rotor was explored to develop ratiometric acidic pH sensor. More information can be found in the Communication by A. Goel et al. onpage 187 in Issue 2, 2016 (DOI:10.1002/ajoc.201500435 ).